2021
DOI: 10.1177/13567667211070013
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Impacts of the Pilgrimage Destination Personality in the Tibetan Region: Case from Larong Wuming Buddhist Academy

Abstract: The present research aims to explore the perceived destination personality of the Larong Wuming Buddhist Academy, a site that is a pilgrimage destination in the Tibetan region of China, and to examine the influence of involvement as an antecedent on the destination personality. This study further investigates the direct and indirect impact of a destination personality on loyalty. A total of 2454 online travel reviews and a convenience sample of 348 usable surveys were analyzed. The personalities of the pilgrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…They further provided empirical evidence for the need to develop a culture-specific destination personality scale in the context of Chinese culture. Also, Liu et al (2022) defined destination personality, namely, the religious, agreeable and ethereal dimensions in the context of pilgrimage destination in the Tibetan region of Chin. They suggested that the BPS may not be fit for direct introduction into the context of the destination personality and that each destination should develop its unique personality characteristic.…”
Section: Moderating Role Of Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…They further provided empirical evidence for the need to develop a culture-specific destination personality scale in the context of Chinese culture. Also, Liu et al (2022) defined destination personality, namely, the religious, agreeable and ethereal dimensions in the context of pilgrimage destination in the Tibetan region of Chin. They suggested that the BPS may not be fit for direct introduction into the context of the destination personality and that each destination should develop its unique personality characteristic.…”
Section: Moderating Role Of Involvementmentioning
confidence: 99%
“…Specifically, festival satisfaction can be defined as "the total sum of the experiences of visitors at the festival" (McDowall, 2011, p. 282). In the literature, there is strong evidence of the relationship between brand, destination and festival personality traits and satisfaction (Chen and Phou, 2013;Chi et al, 2018;Ekinci and Hosany, 2006;Hultman et al, 2015;Liu et al, 2022;G€ uzel et al, 2022;Rocha et al, 2022). Choosing a particular brand with a particular personality allows consumers to express themselves, and the more the brand personality is related to the consumer's personality, the higher the customer satisfaction and loyalty (Aaker, 1999).…”
Section: Festival Personality Satisfaction and Loyaltymentioning
confidence: 99%
See 2 more Smart Citations
“…Destination personality is a complex construct which is difficult to measure. Its relationships with other marketing concepts have been studied in recent studies, such as destination branding Hultman et al, 2017), destination image (Hosany et al, 2006;Papadimitrou et al, 2015;Souiden et al, 2017), destination brand equity (Salehzadeh et al, 2016) and brand attachment (Huang et al, 2017), positioning (Hanna & Rowley, 2019;Kumar & Nayak, 2018), involvement (Chi et al, 2018;Liu et al, 2021), loyalty and behavioral intentions (Ekinci and Hosany, 2006;Baloglu et al, 2014;Pool et al, 2018;Yang et al, 2020;Liu et al, 2021). The relationship of destination personality with self-congruity (e.g., Yang et al, 2022), self-identity or tourist-destination identification (Huaman-Ramirez et al, 2021;Zhang et al, 2022) is another critical issue in the relevant literature, especially if we consider that it may act as a partial mediator on the relationship between destination personality and tourist's behavioral intentions (Usakli and Baloglu, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%